Pendekatan Fenomenologi dalam Studi Islam - Sihabuddin, Sihabuddin (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2020)
Religion is the gift of God Almighty which is intended for humans (Muslims) as a guide to get safety in the world and the hereafter, because in Islam there are rules that must be followed by individuals and groups in order to distinguish between good (constructive-moralist) and which is bad (degradation-immoralis). Nevertheless, studying religion that collaborates science is not something that is prohibited. In fact, the correlation between religion and science is something that is very likely to be carried by religious scholars, including in Islam. Understanding of the Islamic religion which has tended to be “theologically-normative” for decades has closed Islamic thinkers to study the phenomenon of Islam, such as understanding the practices of religious teachings that tend to be ritualistic in each of the Muslims themselves. To understand it, a special method is needed called “phenomenology”, where this method describes the experience of the religious practice of religious adherents consciously of the religious phenomena that are carried out.